Synthesis, Self-Assembly and Photoresponsive Behavior of Liquid Crystals Based on Azobenzene - Yaming Wu; Yuhai Liu; Jianxiang Chen; Runmiao Yang (Crystals, 2021)
A new amphiphilic surfactant (C4-Azo-C5-HDA) was formed by liquid crystals (LCs) based on azobenzene, whose structures were characterized by 1H-NMR spectroscopy. The reversible hydrogelation upon changes in temperature and light exposure was also studied. Under the irradiation of UV light, the trans-isomer of C4-Azo-C5-HDA rapidly photoisomerized to the cis-isomer, resulting in rapid disruption of the gel. The thermotropic liquid crystal behavior of the gelator was investigated via Differential Scanning Calorimetry (DSC) and Polarizing Optical Microscopy (POM). The biocompatibility experiment of multi-stimulus response of the liquid crystal provides a potential driving force for the development of biomaterials.